Co-design, experimentation and assessment of agroecological technologies on dairy farms in the Bobo Dioulasso milkshed (Burkina Faso): Campaign 2024/2025 - Ouattara, Songdah Désiré; Sib, Ollo; Sanogo, Souleymane; Sodre, Etienne; Ouattara, Baba; Vall, Eric (2024)
This report presents the general methodology of the U-OnEDA protocol for the 2024/2025 campaign. Data collection is still in progress at the time of writing this report, which is why this document does not present any results. The full 2024/2025 campaign report will be issued in May 2025, once all the data has been collected and analyzed.